2009
DOI: 10.1080/09541440802413505
|View full text |Cite
|
Sign up to set email alerts
|

The testing effect, collaborative learning, and retrieval-induced facilitation in a classroom setting

Abstract: Two studies were conducted to investigate aspects of the test effect in a tertiary education setting. During weekly tutorial sessions first year psychology students watched a psychobiology video (Phase 1), followed by different video-related activities (Phase 2). In the tutorial 1 week later, students took an unexpected test (Phase 3). In Phase 2 of Study 1, students completed a quiz in small groups (group quiz) or individually (individual quiz), highlighted the video transcript (re-study), or did nothing furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 41 publications
7
81
3
Order By: Relevance
“…The result of better performance due to repeated testing gives support to a bulk of previous literature on the testing effect (see Bangert-Drowns, Kulik & Kulik, 1991;Cranney et al, 2009;Johnson & Mayer, 2009;Leeming, 2002;McDaniel et al, 2007;Vojdanoska, Cranney & Newell, 2009;see also Glover 1989). Although the routine of repeated testing cannot be the philosopher's stone which promises to turn the dust into gold, it may nevertheless enrich the arsenal of the wise teacher willing to raise the standard in the classroom.…”
Section: Implications For Practice and Further Possibilitiessupporting
confidence: 71%
See 1 more Smart Citation
“…The result of better performance due to repeated testing gives support to a bulk of previous literature on the testing effect (see Bangert-Drowns, Kulik & Kulik, 1991;Cranney et al, 2009;Johnson & Mayer, 2009;Leeming, 2002;McDaniel et al, 2007;Vojdanoska, Cranney & Newell, 2009;see also Glover 1989). Although the routine of repeated testing cannot be the philosopher's stone which promises to turn the dust into gold, it may nevertheless enrich the arsenal of the wise teacher willing to raise the standard in the classroom.…”
Section: Implications For Practice and Further Possibilitiessupporting
confidence: 71%
“…On the basis of previous results (e.g., Cranney et al, 2009;Johnson & Mayer, 2009;Karpicke & Roediger,2008;Leeming, 2002;McDaniel et al, 2007;Roediger & Karpicke, 2006a;2006b;Vojdanoska, Cranney & Newell, 2009), the statistical hypothesis is one-sided: the alternative hypothesis is H 1 : The gain score is higher in the EG than in the CG.…”
Section: Design and Hypothesesmentioning
confidence: 99%
“…This interest stems mainly from the fact that testing has been established as one of the most powerful memory enhancers available Karpicke & Roediger, 2008;McDaniel, Roediger et al, 2007). Echoing this general idea, recent research (e.g., Chan, 2009;Chan et al, 2006;Cranney et al, 2009;Pilotti et al, 2009) has reported that testing can enhance retention of both the tested and nontested-related materials. In the current experiment, I have demonstrated that the benefits of RIFA are long-lived.…”
Section: Discussion Chan 12mentioning
confidence: 99%
“…Nevertheless, many studies in various university courses have found a positive connection between the testing and external test results (see Metsämuuronen, 2013;Vojdanoska, Cranney & Newell, 2009;Cranney et al, 2009;Johnson & Mayer, 2009;McDaniel et al, 2007;Leeming, 2002). Bangert-Drowns, Kulik, and Kulik (1991) found, in their meta-analysis, that 83% of the studies showed a positive effect of frequent testing.…”
Section: Testing Effect Related To the Classroom Settingsmentioning
confidence: 99%
“…The testing was of a static type: no feedback was given to the students. Because of convincing previous results (see Metsämuuronen, 2013;Vojdanoska, Cranney & Newell, 2009;Johnson & Mayer, 2009;Cranney et al, 2009;McDaniel et al, 2007;Roediger & Karpicke, 2006a;2006b;Leeming, 2002) the alternative hypothesis is kept one-sided: the gain score in the EG is higher than in the CG.…”
Section: Design and Hypothesesmentioning
confidence: 99%